Impact of peripheral artery disease on prognosis after percutaneous coronary intervention: Outcomes from the multicenter prospective e-ULTIMASTER registry. (March 2022) - Kobo, Ofer; Saada, Majdi; Laanmets, Peep; Karageorgiev, Dimitar; Routledge, Helen; Crowley, Jim; Baello, Pascual; Requena, Javier Balague; Spanó, Fabrizio; Perez, Luis; Jimenez Mazuecos, Jesus Maria; Mamas, Mamas A.; et al.
Abstract: Background and aims: Patients with peripheral artery disease (PAD) represent a high risk group, and have an increased risk of cardiovascular events and worse cardiovascular outcomes. Our aim was to study the impact of PAD among patients undergoing percutaneous coronary intervention (PCI) with a newer-generation thin-strut DES. Methods: In this analysis of the e‐ULTIMASTER registry, patients with and without known PAD undergoing PCI were compared. A propensity-score was used to adjust for differences between the groups. The primary outcome was target lesion failure (TLF): a composite of cardiac death, target‐vessel related myocardial infarction, and/or clinically driven target lesion revascularization at 1‐year follow‐up. Results: Of 33, 880 patients included in the analysis, PAD was present in 2255 (6.7%). Patients with PAD were older (69.0 ± 10.0 vs. 63.8 ± 11.3 years) with a higher burden of comorbidities. Patients with PAD were less likely to present with STEMI (9.6% vs. 21%), and more likely to undergo complex PCI (left main 5.5% vs. 3.0% ostial lesions 10.4% vs . 7.0%, bifurcations 14.5% vs. 12.3% and calcification 26.8% vs. 17.8%). PAD was found to be independently associated with 41% increased risk for TLF. The risk for all cause death and for cardiac death was 75% and 103% higher, respectably. No difference was found in the rates of stent thrombosis, clinically driven target lesion revascularization, or myocardial infarction (MI). Conclusions: Patients with PAD are at higher risk for (cardiac) death post PCI, but not target vessel or lesion repeat revascularizations. The PAD cohort represents a population with a higher risk clinical profile. Further research combining medical and device therapies is needed to further improve the outcomes in this high-risk population. Graphical abstract: Image 1 Highlights: Using the e‐ULTIMASTER PCI registry [n = 33, 880 patients], outcomes were compared according to peripheral artery disease (PAD) 2, 255 (6.7%) or no PAD. Patients with PAD were older with a higher burden of comorbidities, and underwent more complex interventions. PAD was found to be independently associated with 41% increased risk for target lesion failure (TLF). No difference was found in the rates of stent thrombosis, clinically driven target lesion revascularization, or myocardial infarction (MI). Patients with PAD treated with contemporary DES are at higher risk for cardiac death post percutaneous coronary intervention (PCI), but similar repeat revascularization risk.